ANALISIS PUISI “KUCARI JALAN MENUJU RUMAHKU” PADA ANTOLOGI AKU BAWAKAN CINTA BUATMU KARYA CHORY MARBAWI MENGGUNAKAN PENDEKATAN OBJEKTIF - Nur Haliza Fitri; Putri Dini Rawati; Nuraini Detia Putri; Rustam Rustam; Priyanto Priyanto (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
Analyzing literary works is a common thing to do as a process of meaning or giving meaning to literary works with aesthetic intensity; another term is concretization. Various approaches are offered, one of which is an objective approach, namely an approach that focuses on the literary work itself; this approach considers literary works autonomous. As an autonomous structure, a literary work can be understood as a rounded whole with building elements. Therefore, to understand its meaning, a literary work must be analyzed based on its structure, detached from various elements outside the structure of its significance. The poem "Kucari Jalan Menuju Rumahku" in the Anthology Aku Bawakan Cinta Buatmu is formed from a unique and straightforward language order but has a broad meaning and makes readers interested in his work. This study aims to analyze the meaning of the poem entitled " Kucari Jalan Menuju Rumahku" in the Anthology Aku Bawakan Cinta Buatmu by Chory Marbawi and convey the detailed content of the poem so that readers can know the meaning conveyed through this research. This research is also helpful for readers to further develop literary works in the form of poetry. The method used in this study used a descriptive method that examines the content of the meaning of poetry. In addition, the poems in this study were dissected using an objective approach.